The crosstalk between BAT thermogenesis and skeletal muscle dysfunction - Chen, Yao; Hu, Qian; Wang, Changyi; Wang, Tiantian (Frontiers in Physiology, 2023)
Metabolic defects increase the risk of skeletal muscle diseases, and muscle impairment might worsen metabolic disruption, leading to a vicious cycle. Both brown adipose tissue (BAT) and skeletal muscle play important roles in non-shivering thermogenesis to regulate energy homeostasis. BAT regulates body temperature, systemic metabolism, and seretion of batokines that have positive or negative impacts on skeletal muscle. Conversely, muscle can secrete myokines that regulate BAT function. This review explained the crosstalk between BAT and skeletal muscle, and then discussed the batokines and highlighted their impact on skeletal muscle under physiological conditions. BAT is now considered a potential therapeutic target for obesity and diabetes treatment. Moreover, manipulation of BAT may be an attractive approach for the treatment of muscle weakness by correcting metabolic deficits. Theredore, exploring BAT as a potential treatment for sarcopenia could be a promising avenue for future research.